ٹرانس جینڈر بل کی قانونی اور شرعی حیثیت اور مسلمان معاشرے پر اس کے اثرات: ایک علمی وتحقیقی جائزہ: An Academic and Research review of the Legal and Sharīʻah Status of the Transgender Bill and its Impacts on Muslim Society (Al-Qamar, 2023)
Pakistan is an Islamic democratic country. But unfortunately, at different times, different attempts were made to introduce such laws which have nothing to do with Islam, but are completely against Islam. Transgender Act is also one of such laws. It is very burning issue of the time. There are heated comments and discussions about this bill in our academic and political circles. It is really very important and worth considering issue. This bill is a new and self-made bill against the Constitution of Pakistan, Islamic Teachings and our Eastern Traditions. Its effects on Islamic societies and Muslims are very negative and dangerous. The protection of this law endangers the family system of Muslims as well. It is said that according to this bill, any man or woman can change their gender according to their own will and desire. A girl can make herself fake boy and a boy can make himself fake girl. It also means that a girl can change her old name to a boy's name, while a boy can also change his name to a girl's name. Transgender is a modern term. There is no scope for this term in Islam. Researchers say that this paves the way for homosexuality. Research also shows that the Transgender Bill is an un-Islamic, unconstitutional and non-Sharia law that contradicts the objectives of Sharia. Therefore, in this research paper, a scientific and research review will be doing in the light of Quran and Sunnah and rational arguments regarding the illegitimacy of this bill from different points of view and its fatal and destructive effects on the Muslims Societies will be analyzed.
Keywords: Transgender Act; Quran and Sunnah; Sharia; Constitution of Pakistan; Family System; Homosexuality; Western Civilization